(untitled) (Environmental Smoke, 2024)
Herein, we report the first observation of the coral Astrangia solitaria (Le Sueur, 1817) adhered on the polypropylene fishing rope (artificial substrate), collected in the areas of the Great Amazon Reef System (GARS). The specimens of A. solitaria were collected adhered on the fishing rope abandoned in bottom areas associated with the GARS, in the state of Amapá (Northern Brazil) (02°57’54"N; 048°27’50,4"W), during the commercial fishing operations of the red snapper - Lutjanus purpureus (Poey, 1866) - in May 2024. We observed 226 m of lost rope from the illegal lobster trap “caçoeira” adhered (wrapped) in the fish trap called “manzuá”, where we accounted 63 colonies of A. solitaria covering 12.5 cm of this rope. This observation can be associated with a wide range of marine invertebrate adaptations for the use of these types of macroplastics in an anthropized environment.